Pengaruh Beban Kerja dan Stress Kerja Terhadap Kinerja Karyawan di 99 Wedding and Event Organizer - Trikusuma, Ni Komang Asti; Puja, Ida Bagus Putu; Wirata, I Nengah (Journal of Event and Convention Management, 2023)
The formulation of the problem in this research is the effect of workload and work stress on employee performance at 99 Wedding and Event Organizers, either partially or simultaneously. This study uses quantitative research methods, secondary data management obtained from the company and primary data obtained from interviews and questionnaires. The sample in this study amounted to 24 respondents who were distributed to all employees of 99 Wedding and Event Organizers. The data analysis method used was multiple regression analysis, F test, t test and the coefficient of determination. The results showed that there was a positive influence between workload on employee performance at 99 Wedding and Event Organizers with a significance value of 0.001, there was a positive influence between work stress on employee performance at 99 Wedding and Event Organizers with a significance value of 0.004 and there was a positive influence between workload, work stress on employee performance at 99 Wedding and Event Organizers with a significance value of 0.000.